Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Pemadam Kebakaran Kabupaten Solok - Andri B, Alza Syofyan; Taufid, Hidayattul; Syafwandi, Syafwandi (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the effect of work motivation and work discipline on employee performance at the Solok Regency Fire Department. The research method used is quantitative with a survey approach using a questionnaire. The number of respondents was 53 Fire Department employees. Data analysis was carried out in several stages, namely 1) Validity test was tested with Pearson correlation (r count r table). 2) Reliability was tested with Cronbach Alpha ( 0.60 is considered reliable). 3) Normality test to determine whether the data is normally distributed or not 4) T test to determine the effect of each independent variable on the dependent variable. 5) F test to determine the effect of work motivation and work discipline simultaneously on employee performance. 6) Coefficient of Determination (R) to determine how much the independent variable contributes to explaining the dependent variable. Effective leadership, demonstrated by exemplary attitudes, open communication, and participatory decision-making, as well as a conducive work culture such as discipline, responsibility, and teamwork, has been shown to increase employee productivity and work quality. This research provides theoretical and practical contributions in efforts to improve the performance of local government apparatus.